The linear ordering problem exact and heuristic methods in combinatorial optimization - Martí, Rafael (Rafael Cunquero); Reinelt, G. (Gerhard) (Heidelberg, Germany Springer Berlin, 2011)
Exact and heuristic techniques are enhancing our ability to overcome intractable obstacles in the world of optimization. Using the linear ordering problem as an illustration, this text provides a toolkit for tackling a variety of combinatorial dilemmas
Pt. 1. Introduction -- pt. 2. Heuristic Methods -- pt. 3. Meta-Heuristics -- pt. 4. Branch-and-Bound -- pt.5. Branch-and-Cut --pt.6. The Linear Ordering Polytope -- pt.7. Further Aspects
Keywords: Combinatorial optimization; Mathematical optimization; Sequences (Mathematics)